Understanding digital humanities - Berry, David M. (David Michael) (Palgrave Macmillan, 2012)
"Confronting the digital revolution in academia, this book examines the application of new computational techniques and visualisation technologies in the Arts & Humanities. Uniting differing perspectives, leading and emerging scholars discuss the theoretical and practicalchallenges that computation raises for these disciplines"--Provided by publisher.